Analysis of Community Concerns Regarding Solid Waste Disposal - Nelvidawati Nelvidawati Nelvidawati; Maihasni Maihasni; Justin Farrell (LPPM Universitas PGRI Sumatera Barat, 2024)
Solid waste disposal (TPA) in Indonesia have a polluting impact on the environment and people often reject the existence of TPA around them. The community around the Leuwigajah TPA refuses to allow the TPA to be reactivated. The community's rejection was due to concerns. This research is a quantitative descriptive study that analyzes the concerns of the community around the landfill regarding the impact of pollution, health problems and management capabilities. The identities of the respondents included in this research are age, gender, education level and type of work. Male respondents, respondents in the 30-39 year age group, respondents who have completed elementary school and respondents who work as housewives have the greatest number of concerns about the pollution caused, health problems and the inability of managers. Based on the sampling area, the respondents who had the most concerns about pollution, health problems and management incompetence were in Cibungur Village.